2022
DOI: 10.2967/jnumed.122.264456
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Survival Outcomes of177Lu-Prostate-Specific Membrane Antigen Therapy in Patients with Metastatic Castration-Resistant Prostate Cancer with Prior223Ra treatment: The RALU Study

Abstract: The RAdium LUtetium (RALU) study evaluated the feasibility of sequential alpha and beta emitter use in patients with bone-predominant metastatic castration-resistant prostate cancer.Methods: This pre-planned, interim, retrospective analysis investigated safety and survival outcomes with lutetium-177-PSMA ( 177 Lu-PSMA) in patients treated with prior radium-223 ( 223 Ra). Results: Forty-nine patients were evaluated. Patients received a median of 6 223 Ra injections; 59% of patients received 4 177 Lu-PSMA cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…PSA50, PSA-PFS and OS presented positive correlation with uptake in salivary glands either in a visual or quantitative scale ( P < 0.005), with good interreader reproducibility (k = 0.68). 40 Rahbar et al 41 published the interim analysis of 49 patients of the RALU retrospective trial. They found that a median of 6 doses of 223 Ra-RaCl 2 followed by 177 Lu-PSMA-617 is feasible with additional PSA30 decline in 29% and grade ≥3 AE occurring in 18% of mCRPC patients.…”
Section: Prospective or Retrospective Studies Using Psma-617 Or Psma-...mentioning
confidence: 99%
See 3 more Smart Citations
“…PSA50, PSA-PFS and OS presented positive correlation with uptake in salivary glands either in a visual or quantitative scale ( P < 0.005), with good interreader reproducibility (k = 0.68). 40 Rahbar et al 41 published the interim analysis of 49 patients of the RALU retrospective trial. They found that a median of 6 doses of 223 Ra-RaCl 2 followed by 177 Lu-PSMA-617 is feasible with additional PSA30 decline in 29% and grade ≥3 AE occurring in 18% of mCRPC patients.…”
Section: Prospective or Retrospective Studies Using Psma-617 Or Psma-...mentioning
confidence: 99%
“…The median OS was 12.6 months and 31.4 months, respectively, after starting PSMA-RLT and 223 Ra-RaCl 2 ( P < 0.005), with a median interval of 9.3 months between studies. 41 Similar to the RALU study, Baumgarten et al 42 retrospectively evaluated 28 men with progressive mCRPC who received 177 Lu-PSMA-617 after 223 Ra-RaCl 2 administration. Patients with high bone tumor burden (>20 lesions) had a significantly shorter OS (14 vs 28 months, P < 0.045).…”
Section: Prospective or Retrospective Studies Using Psma-617 Or Psma-...mentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with a high osseous metastatic burden in PSMA PET/CT have an overall worse prognosis and a higher risk of myelotoxicity when treated with 177Lutetium-PSMA-617 (Lu PSMA) [ 31 ]. However, the recent publication of an interim analysis of the RALU study shows the safety and feasibility of the sequential use of first Ra223 (Ra223 and then Lu PSMA [ 32 ], both myelotoxic therapies). Moreover, the findings from the WARMTH study showed that a prior therapy with 223Ra had a positive impact on overall survival in patients who were subsequently treated with LuPSMA [ 33 ].…”
Section: Discussionmentioning
confidence: 99%